Functional and Aesthetic Outcomes of Septal Reconstructions: Results of a Prospective Longitudinal Outcome Study - van Dam, Victor S.; van Zijl, Floris V.W.J.; Lohuis, Peter J.F.M.; Datema, Frank R. (Facial Plastic Surgery, 2023)
In order to correct severe septal deformities, complete septal reconstruction is often required to achieve the desired functional and aesthetic results. Several different techniques have been described. Systematic evaluation of the long-term results is crucial to assess and improve the quality of these surgical techniques. A custom-built dashboard (the rhinoplasty health care monitor [RHM]) was used for prospective and longitudinal outcome evaluation of the septal reconstruction. The RHM includes the Nasal Obstruction Symptom Evaluation (NOSE) scale for nasal obstruction and the Utrecht Questionnaire (UQ) for aesthetic outcome results. In total, 58 patients were included for septal reconstructive surgery. The mean preoperative NOSE scale scores decreased from 67.8 ± 19.1 to 12.2 ± 17.5, 1 year after surgery. Mean preoperative UQ scores went from 12.3 ± 6.4 to 6.2 ± 2.7. The beneficial functional and aesthetic effects of the techniques that we currently use to reconstruct the septum are efficient in terms of function and aesthetics.
Keywords: septal reconstruction; outcomes; PROM; rhinoplasty